An Update on Secondary Metabolites from Glycyrrhiza Species - Azizuddin Shaikh (Journal of Basic & Applied Sciences, 2017)
Secondary metabolites have been obtained from the Glycyrrhiza species (Fabaceae) including G. glabra, G. echinata, G. uralensis, G. triphylla and G. macedonica. These compounds 1-25 belong to the classes, steroid, saponin, flavonoid, flavonoid glycoside, triterpenic acid, coumarin, phenolic derivative, chalcone and chalcone glycoside. This review will describe the isolated compounds 1-25, obtained from Glycyrrhiza species with their biological activities up to 1966.